Congo Red Effects on Detoxification and Metabolic Enzymes in Rainbow Trout (Oncorhynchus mykiss Walbaum, 1792) - Durali Danabas; Nuran Cikcikoglu Yildirim; Numan Yildirim; Onder Aksu (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to evaluate the activities of the biotransformation enzymes (Glutatyon S-Transferase (GST) and cytochrome P450 (CYP1A1)) and metabolic enzyme (Lactate dehydrogenase-LDH) in the liver of rainbow trout (Oncorhynchus mykiss) after 24 and 48 hour exposure to 0.5, 1.0 and, 2.0 mg l-1 of Congo red (CR). Enzyme activities were determined by using commercial kits with ELISA method. Congo red altered the activities of GST, CYP1A, and LDH enzymes in liver tissue of O. mykiss in a dose-dependent manner. The statistical differences in GST activities among the groups for 24 and 48 h were significant, but, LDH activities were significant for only 24 h. Exposure duration of CR didn’t affect the biochemical response of rainbow trout. Thus, CR exposure changed the biotransformation and metabolic enzymes, and the changes of these enzymes activities may be used as a potential bioindicator of the CR exposure.